Socio-economic status and use of social media by undergraduates in Redeemer’s University, Osun State, Nigeria (2020)
There is a mass appeal of social media on the Internet in recent times. Perhaps, this is due to the gradually increasing amount of time that undergraduate students spend on the Internet to the detriment of their studies. The study, therefore, investigated socioeconomic Status and use of social media by undergraduates in Redeemer's University, Osun State, Nigeria. The study adopted a descriptive survey research design of the correlational type. Data were collected from 121 undergraduates of the Redeemer's University with the use of a structured questionnaire with Cronbach alpha [a = 0.78J. Data analysis was done using frequency count and percentage distribution to answer the research question 1-3 white the Pearson's Correlation Coefficient at 0.05 level of significance was used to answer the research question 4. The main social media use by the undergraduates includes Facebook (100.0%), WhatsApp (86.8%), Ebuddy and (82.6%). Socio-economic Status of affluence for undergraduates' use of social media include: dignifying parental occupation, parental educational qualification, and steady monthly allowance. The students used social media for chatting (71.9%), checking through wall/news (76.9%), sharing Information, files, photos, and documents (100.0%). Socio-economic Status has significant relationship with use of social media (r = .816”; df = 120; p <0.05). The undergraduates use different types of social media for leisure, entertainment and knowledge sharing. It was, therefore, recommended that university authorities should seek to appreciate the use of social media for academic purposes; researchers should focus more on studies of social media use in education, and so on.